An unusual hydroxy-substituted mononuclear nickel(II) complex with a tetradentate Schiff base: Synthesis, spectroscopy, electrochemistry, crystallography, DNA binding, and theoretical investigation. (29th March 2015) - Gupta, Sushil K.; Anjana, Chanda; Sen, Neha; Butcher, Ray J.; Jasinski, Jerry P.; Golen, James A.
Graphical abstract: An experimental and theoretical study of sterically demanding ligands based on 4-alkyl-2, 6-dibenzoylphenol and their nickel(II) complexes (1, 2 ) is presented. Complex2 is the unusual hydroxy-substituted mononuclear nickel(II) complex with tetradentate Schiff base. The compounds bind to CT DNA via intercalation. Abstract: The 2:1 Schiff base condensates of 4-methyl-2, 6-dibenzoylphenol (mdbpH) or 4- tert -butyl-2, 6-dibenzoylphenol (bdbpH) with ethane-1, 2-diamine, L 1 H2 andL 2 H2, respectively, were isolated and used to prepare nickel(II) derivatives. The resultant complexes, [NiOC6 H2 (CH3 )(COC6 H5 )2 (C6 H5 CN(CH2 )2 NCC6 H5 )] (1 ) and [NiOC6 H2 ( t -Bu)(COC6 H5 )2 (C6 H5 CN(CH2 CHOH)NCC6 H5 )] (2 ), have been characterized by elemental analyses, conductivity measurements, mass spectrometry, IR, 1 H and 13 C NMR and electronic spectroscopy, cyclic voltammetry, and X-ray crystallography. The ligand precursors and complexes all crystallize in the P 1 ¯ space group. In1 and2, the coordination at Ni II, which shows a slight distortion from square planar towards tetrahedral geometry, comprises two phenolato O and two imine N atoms of the tetradentate (L 2− ) unit. Density Functional Theory (DFT) calculations provide a satisfactory description of the structural and electronic properties of the new compounds. Electrochemical studies of1 and2 are described. The interactions of complexes1 and2, and ligandsL 1 H2 andL 2 H2, with calf thymus DNA were investigated by UV–Vis absorption titrations and cyclic voltammetric methods. Complexes1 and2, and ligandsL 1 H2 andL 2 H2 bind to DNA via intercalation; the binding affinity of complex1 is higher than that of complex2 and of the ligand precursorsL 1 H2 andL 2 H2 .